On-line microfluidic sensor integrated with an enzyme-modified pre-cell for the monitoring of paracetamol in pharmaceutical samples - Messina, Germán Alejandro (2006)
An on-line microfluidic sensing device with an enzyme-modified pre-cell coupled to an amperometric detector for the monitoring of paracetamol in pharmaceutical formulations is described. Horseradish peroxidase (HRP) [EC 1.11.1.7], immobilized on a 3 μl pre-cell, in presence of hydrogen peroxide catalyses the oxidation of paracetamol to N-acetyl-p-benzoquinoneimine. The electrochemical reduction back to hydroquinone is detected on glassy carbon electrode surface at -0.10 V. The recovery of paracetamol from 10 samples ranged from 99.00 to 101.10%. This method could be used to determine paracetamol concentration in the range 0.35-100 μM (r = 0.997) with a limit of detection of 3.0 × 10-7 M and a relative standard deviation was less than 4.1% (n = 8). The method was successfully applied for the processing of as many as 20 samples per hour of paracetamol in pharmaceutical formulations.